Impact of the Juan Fernandez Ridge on the Pampean Flat Subduction Inferred From Full Waveform Inversion. Issue 21 (8th November 2021) - Gao, Yajian; Yuan, Xiaohui; Heit, Benjamin; Tilmann, Frederik; van Herwaarden, Dirk‐Philip; Thrastarson, Solvi; Fichtner, Andreas; Schurr, Bernd
Abstract: A new seismic model for crust and upper mantle of the south Central Andes is derived from full waveform inversion, covering the Pampean flat subduction and adjacent Payenia steep subduction segments. Focused crustal low‐velocity anomalies indicate partial melts in the Payenia segment along the volcanic arc, whereas weaker low‐velocity anomalies covering a wide zone in the Pampean segment are interpreted as remnant partial melts. Thinning and tearing of the flat Nazca slab is inferred from gaps in the slab along the inland projection of the Juan Fernandez Ridge. A high‐velocity anomaly in the mantle below the flat slab is interpreted as relic Nazca slab segment, which indicates an earlier slab break‐off triggered by the buoyancy of the Juan Fernandez Ridge during the flattening process. In Payenia, large‐scale low‐velocity anomalies atop and below the re‐steepened Nazca slab are associated with the re‐opening of the mantle wedge and sub‐slab asthenospheric flow, respectively. Plain Language Summary: Taking advantage of the abundant information recorded in seismic waveforms, we imaged the seismic structure of the crust and upper mantle beneath central Chile and western Argentina, where the oceanic Nazca slab is subducting beneath the South American plate. The subducted Nazca slab is almost flat at a depth of 100–150 km in the north of the study area below the Pampean region, where the Juan Fernandez seamount ridge is subducting as part of the Nazca slab. The slab steepens again in the south in the Payenia region. Our model reveals pronounced low‐velocity anomalies within the Pampean flat slab along the inland projection of the Juan Fernandez Ridge, indicating that the Pampean flat slab is thinned or even torn apart. A high‐velocity anomaly is imaged beneath the flat slab, representing a former slab segment that was broken off during the slab flattening process and was overridden by the advancing young slab. Our model suggests a causal relationship between the oceanic ridge subduction and the flat slab formation. In the Payenia region, the slab re‐steepening resulted in the re‐establishment of the mantle wedge and induced hot mantle flow below the slab, which are characterized by low‐velocity anomalies in the model. Key Points: A new seismic model for the crust and upper mantle beneath central Chile and western Argentina is presented Thinning and tearing within the Pampean flat slab is detected along the inland projection of the Juan Fernandez Ridge A relic slab is imaged beneath the Pampean flat slab, reflecting slab break‐off during the flattening process